1 Clement: a reader's edition - Klemens, I., Papst ca. 1. Jh. (Catholic University of America Press, 2020)
Intro -- Table of Contents -- Introduction -- Acknowledgments -- 1 Clement -- Dictionary of Words Occurring Frequently In Early Christian Greek Literature -- Scriptural Quotations and Allusions in 1 Clement -- Bibliography.